A facile high‐performance SERS substrate based on broadband near‐perfect optical absorption. (1st June 2015) - Yan, Zhendong; Du, Wei; Tu, Linlin; Gu, Ping; Huang, Zhong; Zhan, Peng; Liu, Fanxin; Wang, Zhenlin
Abstract : Plasmonic systems based on metal nanoparticles on a metal film with high optical absorption have generated great interests for surface‐enhanced Raman scattering (SERS). In this study, we prepare a broadband‐visible light absorber consisting Au nanotriangles on the surface of a continuous optically opaque gold film separated with a dielectric SiO2 layer, which is a typical metal‐insulator‐metal (MIM) system, and demonstrate it as an efficient SERS substrate. The MIM nanostructure, prepared using nanosphere lithography with a very large area, shows a broadband with absorption exceeding 90% in the wavelength regime of 630–920 nm. We observe an average SERS enhancement factor (EF) as large as 4.9 × 10 6 with a 22‐fold increase compared to a single layer of Au nanotriangles directly on a quartz substrate. A maximum SERS EF can be achieved by optimizing the thicknesses of the dielectric layer to control the optical absorption. Owing to the simple, productive, and inexpensive fabrication technique, our MIM nanostructure could be a potential candidate for SERS applications. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A broadband near‐perfect optical absorber consisting Au nanotriangles on the surface of an optically opaque gold film separated with a dielectric SiO2 layer serves as an effective surface‐enhanced Raman scattering (SERS) substrate. A maximum SERS enhancement factor can be achieved by optimizing the thicknesses of the dielectric layer to control the optical absorption.